My day Rainbow Books - Siede, George; Siede, George; Publications International, Ltd. (Lincolnwood, Illinois Publications International, Ltd., 1995)
Introduces young children to daily routines through simple text and colourful illustrations, promoting recognition of everyday activities.
Board book designed for toddlers; features vibrant illustrations depicting daily activities
Ages 0-3
Keywords: Children's daily activities, Board books, Picture books for children